Pengaruh Penambahan Berbagai Bahan Organik pada Media Tanam Sub Soil Terhadap Pertumbuhan Bibit Petai (Parkia speciosa): Effect of Adding Various Organic Ingredients to The Media Planting Sub Soil for Growth Petai Seeds (Parkia speciosa - Hamzah, Hamzah; Hardiyanti, Rizky Ayu; Handayani, Rajjitha; Rumondang, Jenny; Utari, Indah Tri (Fakultas Kehutanan Universitas Jambi, 2024)
ABSTRACT Petai is a plant that belongs to the MPTS (Multi Purpose Tree Species) plant type which can be used multiple times for both wood and non-wood. Petai also has benefits from an economic perspective (fruit and wood) and ecology (legume plants fertilize the soil) so it needs to be cultivated well. There are several factors that influence the quality of cultivation results, one of which is the planting media. The planting medium used is soil in the sub-soil layer as an alternative to top soil. However, this layer is not as fertile as the top soil layer, so it is necessary to add soil improving materials (Ameliorants), for example organic materials. This research aims to analyze the effect of adding various organic materials to sub-soil planting media on the growth of Petai seedlings and to obtain the best organic material composition to add to sub-soil planting media which can have a real influence on the growth of Petai seedlings. This research was carried out for 3 months using a completely randomized design (CRD) method with 1 factor, namely planting media (M) consisting of 5 treatments, namely m1 (Sub soil + compost 3:1), m2 (Sub soil + husk charcoal 2:1), m3 (Sub soil + Cocopeat 2:1), m4 (Sub soil + Boiler ash 4:1) and m5 (Sub soil + Laying chicken manure + Sand 1:2:1). The best organic material composition to add to the sub soil planting medium is cocopeat (2:1). Keywords: petai, planting media, organic materials. ABSTRAK Petai merupakan tumbuhan yang tergolong dalam jenis tanaman MPTS (Multi Purpose Tree Species) yang dapat dimanfaatkan secara ganda baik kayu maupun non kayunya. Petai juga memiliki manfaat dari segi ekonomi (buah dan kayunya) maupun ekologi (tumbuhan legum menyuburkan tanah) sehingga perlu dibudidayakan dengan baik. Ada beberapa faktor yang mempengaruhi kualitas hasil budidaya salah satunya media tanam. Media tanam yang digunakan adalah tanah pada lapisan sub soil sebagai alternatif pengganti tanah top soil. Namun, lapisan ini tidak sesubur lapisan top soil sehingga diperlukan penambahan bahan pembenah tanah (Amelioran) contohnya bahan organik. Penelitian ini bertujuan untuk menganalisis pengaruh penambahan berbagai bahan organik pada media tanam sub soil terhadap pertumbuhan bibit petai serta untuk mendapatkan komposisi bahan organik terbaik untuk ditambahkan ke media tanam sub soil yang dapat memberikan pegaruh nyata dalam pertumbuhan bibit Petai. Penelitian ini dilaksanakan selama 3 bulan dengan menggunakan metode rancangan acak lengkap (RAL) 1 faktor yaitu media tanam (M) yang terdiri dari 5 perlakuan yaitu m1 (Sub soil + kompos 3:1), m2 (Sub soil + arang sekam 2:1), m3 (Sub soil + Cocopeat 2:1 ), m4 (Sub soil + Abu boiler 4:1 ) dan m5 (Sub soil + Pupuk kandang ayam petelur + Pasir 1:2:1). Komposisi bahan organik terbaik untuk ditambahkan ke dalam media tanam sub soil adalah cocopeat (2:1). Katakunci: petai, media tanam, bahan organik.